Comparison of Two Bone-Preparation Methods for Radiocarbon Dating: Modified Longin and Ninhydrin. Issue 6 (28th December 2017) - Dumoulin, J-P; Messager, C; Valladas, H; Beck, L; Caffy, I; Delqué-Količ, E; Moreau, C; Lebon, M
ABSTRACT: In this paper, first results comparing modified Longin and ninhydrin collagen extraction methodologies are presented. The goal of this study is to investigate the bones of several species with different ages, preservation conditions, and collagen contents to determine the most suitable preparation method. Different types of samples are used such as VIRI samples, previously dated bones, and background samples. Each bone has undergone elemental analysis, infrared analysis, and 14 C measurement. The results are presented and the advantages and disadvantages of each preparation method are discussed. In general, results obtained by the two methods are in accordance with the consensus value for 2σ uncertainty. For VIRI I and a mammoth bone, the ninhydrin preparation gives, respectively, 8450±70 BP and 14, 870±60 BP whereas the modified Longin process gives 8365±45 BP and 14, 750±100 BP in agreement with the expected values. From the experimental point of view, the modified Longin process is easier to implement than the ninhydrin protocol. From this approach, we can conclude that the modified Longin process could be preferred in most cases and particularly when the amount of bone is small and the sample is not too contaminated.